An SNP Mutation of Gene RsPP Converts Petal Color From Purple to White in Radish (Raphanus sativus L.) - Liu, Dongming; Wei, Xiaochun; Sun, Dongling; Yang, Shuangjuan; Su, Henan; Wang, Zhiyong; Zhao, Yanyan; Li, Lin; Liang, Jinfang; Yang, Luming; Zhang, Xiaowei; Yuan, Yuxiang (Frontiers in Plant Science, 2021)
As the important pigments determining flower color in many plants, anthocyanins also possess some crucial functions in attracting pollinators and reducing abiotic stresses. Purple and white are the two common color for radish petal. In this study, two cDNA libraries constructed with purple and white petal plants were sequenced for transcriptome profiling. A total of 8546 DEGs between the parental lines were obtained. Function enrichment of DEGs revealed a number of pathways and terms in biological processes, cellular components, and molecular functions that were related to plant pigment metabolism, suggesting that there may be a group of common core genes participated in petal coloration. BSA-seq aided with NGS of two DNA pools revealed that the radish purple petal gene (RsPP) was located on chromosome 7. with genotyping of 617 F2 population plants, gene RsPP was further confined to a region of 93.23 kb. Transcriptome and sanger sequencing anslysis further helped to identify gene Rs392880 as the target gene. These results will aid in elucidating the molecular mechanism of plant petal coloration and developing strategies to modify flower color through genetic transformation.